2016
DOI: 10.1007/s11136-016-1332-4
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal assessment of health related quality of life of HIV infected patients treated for tuberculosis and HIV in a high burden setting

Abstract: We found that assessment of HRQoL of participants in TB-HIV treatment using the FAHI instrument was useful in evaluating treatment responses. It showed improvement consistent with decrease in adverse events and signs and symptoms of TB. Number and type of AEs was related to lower HRQoL in spite of TB cure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 35 publications
0
12
0
Order By: Relevance
“…In contrast, a study from South Africa reported greater impairment in physical functioning, but better mental health, among TB/HIV co-infected patients [46]. Another study from South Africa showed overall improvement in QOL with therapy in TB/HIV coinfected patients [47]. This improvement appeared similar among those receiving, and not receiving concomitant anti-retroviral therapy.…”
Section: Tb and Human Immunodeficiency Virus (Hiv) Co-infectionmentioning
confidence: 88%
See 2 more Smart Citations
“…In contrast, a study from South Africa reported greater impairment in physical functioning, but better mental health, among TB/HIV co-infected patients [46]. Another study from South Africa showed overall improvement in QOL with therapy in TB/HIV coinfected patients [47]. This improvement appeared similar among those receiving, and not receiving concomitant anti-retroviral therapy.…”
Section: Tb and Human Immunodeficiency Virus (Hiv) Co-infectionmentioning
confidence: 88%
“…This 26-item instrument evaluates QOL across four domains – Physical, Psychological, Social relationships, and Environment. Some other generic scales used include Medical Outcome Survey (MOS) [9] Social Functioning 12 (SF-12) [32,43], variants of the WHOQOL scale family [19,44,45], and other uncommon or in-house instruments [46], [47], [48].…”
Section: Instruments For Describing and Quantifying Qol In Tbmentioning
confidence: 99%
See 1 more Smart Citation
“…The 15 selected articles were published between 2009 and 2019, being two publications in 2009 (13)(14) , four in 2012 (7)(8)(15)(16) , three in 2013 (17,19) , one in 2014 (20) , one in 2015 (21) , one in 2016 (22) , two in 2018 (23)(24) and one in 2019 (25) . As for the journal, the articles have been published in 13 different ones, with emphasis on Health and Quality of Life Outcomes (14,16) and The International Journal of Tuberculosis and Lung Disease (19,20), with two publications each.…”
Section: Resultsmentioning
confidence: 99%
“…Tuberculosis can significantly reduce individuals’ QOL (Brown et al 2015; Guo, Marra & Marra 2009), but QOL can improve over time with successful TB management (Guo et al 2009; Mthiyane et al 2016). An issue that may contribute to the reduction in QOL is the effect that PTB has on individuals’ lung function.…”
Section: Introductionmentioning
confidence: 99%